Stranded - MacLeod, Bracken (Tor, A Tom Doherty Associates Book, 2016)
"Badly battered by an apocalyptic storm, the crew of the Arctic Promise find themselves in increasingly dire circumstances as they sail blindly into unfamiliar waters and an ominously thickening fog. Without functioning navigation or communication equipment, they are lost and completely alone. One by one, the men fall prey to a mysterious illness. Deckhand Noah Cabot is the only person unaffected by the strange force plaguing the ship and her crew, which does little to ease their growing distrust of him. Dismissing Noah's warnings of worsening conditions, the captain of the ship presses on until the sea freezes into ice and they can go no farther. When the men are ordered overboard in an attempt to break the ship free by hand, the fog clears, revealing a faint shape in the distance that may or may not be their destination. Noah leads the last of the able-bodied crew on a journey across the ice and into an uncertain future where they must fight for their lives against the elements, the ghosts of the past and, ultimately, themselves" --